Simple laboratory-made piezoelectric sensors for detection of selected gaseous and/or vapor sample - Amnat Ruangchaiwat (Science Faculty of Chiang Mai University, 2019)
A very simple laboratory made prototype piezoelectric transducer (PZT) or sensor is described using inexpensive materials and equipment easily available in Chiang Mai and in the laboratory. Initially, experiments are carried out using a single cell device constructed in this laboratory afterwards a double-cell device is modified from the prototype device for measuring gaseous / vapour contaminants in air. The PZT detectors were tested for detection of SO2 on the basis of the best known SO2 detection using triethanolamine as coating material. It was found that the dual-cell device was more sensitive to SO2 (48 Hz / ppm) than the single-cell one (6 Hz / ppm). Optimal conditions for the PZT detector were also investigated. The AT-cut quartz crystals with circular shape having thin film gold electrodes on both sides were employed. It was shown that the 10 MHz crytal coated with triethanolamine was more sentitive than the 6 MHz quartz crystal and hence the 10 MHz quartz crystal was selected as optimum. Selectivity of the PZT detector can be achieved by changing the coating materials. Under suitable conditions, choice of appropriate coating materials could be achieved for a number gaseous / vapour samples. The proposed PZT sensors using selective coatings were successfully applied for detection of SO2 and methanol with satisfactory results.